WOMEN STRUGGLE IN ALI SMITH â€œHOW TO BE BOTHâ€ NOVEL (PANOPTICON: Journal of English Studies, 2022)
This study analyzes the struggles of women experienced by the two main characters in the novel How to be Both by Ali Smith. This study uses the Virginia Wolf theory, the inheritance of gender inequality from a mother to her child and will be passed back to her child. The author uses a qualitative approach to analyze and identify the struggles of women in the novel How to be Both. Furthermore, the theory is also used to find out how the main character does to overcome the struggle of a woman. This research has the result that a woman will continue to inherit gender inequality from her parents. Therefore, the mother of the main character in this novel teaches her child to be an independent woman. Unfortunately the mother died when the main character was only 16 years old. The main character is in a crisis because his mother died. Furthermore, the father chose to go to calm himself rather than comfort his son. But the main character tries to learn from what her mother has taught her about being an independent woman. Furthermore, there are several friends from the main character who provide support to face the crisis. Finally the main character managed to get out of his crisis and could accept his mother's death. Keyword:, Woman struggle, Novel, Feminism , Virginia Wolf.